MERDEKA BELAJAR DALAM MASYARAKAT 5.0 - Houtman, Houtman (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract—Freedom of learning that is currently booming at the moment, is essentially an effort to understand the entire acquisition and implementation of education policies to see the value or results of learning that enhance one's competency abilities. Accreditation is also not a benchmark for an institution's ability to assess quality outcomes. As a result, there needs to be an appropriate policy to measure the capabilities gathered. Indeed, of course this is not spared from the lack of agreement of the majority of people on this policy which considers that the compilation of policies takes place many students are too easy to learn while no longer following the National Examination (UN) which is actually a benchmark according to the questions in accordance with a curriculum that applies to every era. This of course coincides with